Pengetauan Ibu Hamil Tentang HIV/AIDS Dengan Sikap Ibu Hamil Terhadap Konseling dan Tes HIV/AIDs secara Sukarela (KTS): RELATIONSHIP KNOWLEDGE OF PREGNANT WOMEN ABOUT HIV/AIDS WITH ATTITUDE OF PREGNANT WOMEN TOWARDS VOLUNTARY HIV/AIDS COUNSELING AND TESTING (KTS) - Intan Pujilestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
HIV/AIDS is a global health problem that is increasingly widespread today. The number of cases of Human Immunodeficiency Virus (HIV) in 2021 is 36,902 cases and the majority of sufferers are of productive age. Most HIV case sufferers come from the age range of 25-49 years with a percentage of 69.7% in 2021 then 20-24 years of age 16.9% and HIV sufferers over 50 years of 8.1%, ages 15-19 years by 3.1%. The number of cases (of AIDS) was 5750 cases and the majority of sufferers were in the age range of 30-39 years with the aim of knowing whether there was a relationship between pregnant women's knowledge about HIV/AIDS and the attitude of pregnant women towards voluntary counseling and testing of HIV/AIDS (KTS). ) at the Cipageran Health Center, Cimahi City. The research method used is descriptive-analytic with a cross-sectional approach. The population in this study were all pregnant women at the Cipageran Health Center in May as many as 76 pregnant women. The sample in this study used a total sampling technique. Measuring the knowledge and attitudes of pregnant women using a research instrument (questionnaire). The results showed that of the 76 pregnant women, the majority of pregnant women who had less knowledge about HIV/AIDS, 10 pregnant women (83.3%) had a negative attitude towards KTS. asked her to get tested for HIV/AIDS as early as possible to prevent transmission of HIV/AIDS from mother to child.